Social Action in Suroan Tradition in Javanese Society - Fadlan, M; ., Sudjarwo; Sinaga, Risma Margaretha (Journal of Advanced Research in Humanities and Social Sciences; Vol 7 No 1 (2020): Journal of Advanced Research in Humanities and Social Science, 2020)
Suroan is known as a tradition which resulting from acculturation between Saka and Islamic calendar. This tradition is performed to beg blessings and protections from misery and disasters. The implementation of Suroan became a custom in society and involving some trusted agents through social actions. However, most of Suroan performed in society is not in accordance with its true meaning. Regarding with this problem, this research has purpose to obtain the action in the Suroan tradition. The method used is descriptive qualitative with the kind of research is ethnography using Miles and Huberman’s interactive model. The data is collected through interview and observation in Bangunharjo, Taman Sari village. The result shows that social actions performed by Bangunharjo society are: a) traditional action through Suroan implementation is performed; b) affective action in a form of burial of the goat’s head, group prayers and puppet shows; c) instrument rational action in a form of physic, material, and emotional involving; d) rational action of value in a form of ubarampe . Thus, it can be concluded that Bangunharjo society still conserving Suroan tradition.